Study on tire tread design effect onto Tire-road contact behavior through FEM - Amirul Hakim, Sufian; Tan, Zi Xun; Mohd Noor Syukri, Zainal Abidin; Ahmad Shahir, Jamaludin; Mohd Nizar, Muhd Razali (Springer Singapore, 2021)
The characteristics of the interaction between the tire and the road pavement surface are one of the important aspects that must be taken into account in maintaining the safety of driving. Although the tire tread design might have a significant effect onto the contact behavior whereas various design of tire tread available in the market, there is still lacking of understanding on its relationship to tire performance. Thus, the objective of the study is to simulate tire-road contact behavior related to tire tread design utilizing Finite Element Analysis. In the study, several basic design of tire tread had been proposed, and modelled for FEM application. The simulation condition chosen was based on the domestic application, where vehicle ride by average persons was taken into consideration. It is shown that, tread design has a direct effect onto stress distribution inside the tire structure, which cause variation of deformation behavior. The stress distribution is well distributed inside tire and higher intensity 4.0 MPa can be estimated between tire and road in vertical tread designed tire compared to other chosen tire tread designed. This is due to constantly large contact area between tire and road, giving the chance for the force to be distributed inside the tire structure. The estimated stress distribution might have an affect onto tire contact performance, as higher intensity contact stress might mean higher effective contact, while large distribution might mean better stability where force is distributed nicely inside the tire structure.